2018
DOI: 10.1016/j.bbmt.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of T Cell Exhaustion by the First Donor Lymphocyte Infusion Is Associated with the Persistently Effective Antileukemic Responses in Patients with Relapsed AML after Allo-HSCT

Abstract: Donor lymphocyte infusion (DLI) is an effective approach to treat acute myelogenous leukemia (AML) relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) that significantly improves the survival of relapsed patients. However, the mechanism of an effective antileukemic response following DLI in AML relapse remains elusive. Here, we investigated the role of T cell exhaustion in AML relapse after allo-HSCT in prospective cohorts of 41 patients with the first AML relapse and 41 nonrelapsed AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Coherently, it has been shown that sorafenib may indirectly regulate the activation of CD8+ T-lymphocytes and natural killer cells (NKs) by restoring the production of interleukin-15 (IL-15) in FLT3-ITD-mutated clones (Figure 1) [14]. In the leukemic clone, sorafenib activity may also be extended to an increase of IFN-γ production, which may reverse the downregulation of MHC Class II, known to be involved in post-allo-HSCT relapse [18]. The data regarding sorafenib activity on T-regs are conflicting.…”
Section: Flt3 Inhibitorsmentioning
confidence: 99%
“…Coherently, it has been shown that sorafenib may indirectly regulate the activation of CD8+ T-lymphocytes and natural killer cells (NKs) by restoring the production of interleukin-15 (IL-15) in FLT3-ITD-mutated clones (Figure 1) [14]. In the leukemic clone, sorafenib activity may also be extended to an increase of IFN-γ production, which may reverse the downregulation of MHC Class II, known to be involved in post-allo-HSCT relapse [18]. The data regarding sorafenib activity on T-regs are conflicting.…”
Section: Flt3 Inhibitorsmentioning
confidence: 99%
“…Post‐transplant AML relapse is driven in part by loss of leukemic‐specific T cells and loss of T cell function. DLI has been found to increase anti‐leukemic T cells, but also reverses T cell exhaustion through increased IFN‐γ production and reduced T cell inhibitory receptors, such as programmed cell death protein 1 (PD‐1) and T cell immunoglobulin and mucin domain 3 (Tim‐3) . As with allo‐SCT, the major obstacle with DLI is to maximize the GVL effect while minimizing GVHD.…”
Section: DLImentioning
confidence: 99%
“…Sorafenib has been found to increase IL‐15 production in mutant FLT3‐ITD + leukemia cells, which enhances the GVL effect by augmenting CD8 + CD107a + IFN‐γ − + T cells with features of longevity—that is, high levels of Bcl‐2 and low levels of PD‐1. Sorafenib also increases IFN‐γ production, particularly in responders, which may reverse the downregulation of MHC Class II that has been implicated in AML relapse following non‐haploidentical transplant . In a study involving 53 patients with FLT3‐ITD AML (51 with relapsed or refractory disease with 29 having undergone prior allo‐SCT) who were treated with sorafenib monotherapy, 15 patients (23%) achieved complete remission, including seven patients (24%) with prior allo‐SCT.…”
Section: Other Therapies With Immunomodulatory Activitymentioning
confidence: 99%
“…To minimalize the side effects mediated by the recognition of fragment crystallizable (Fc) region, atezolizumab and durvalumab have a point mutation in the Fc domain; thus, they did not induce the cytotoxicity of the antibody-dependent cellular cytotoxicity, nor the complement-dependent cytotoxicity. The upregulation of checkpoint molecules was observed after alloHSCT and therapy with hypomethylating agents, pointing to a potential clinical application in these settings [53,54]. Moreover, a higher PD-1 expression on T cells was strongly associated with leukemia relapse, post-alloHSCT [55].…”
Section: Inhibition Of Pd-1/pd-l1 In Amlmentioning
confidence: 99%